Impact of a full-scale mass casualty exercise on hospital staff and implications for future preparedness: a pre-post study - Forst, Maik von der; Germann, Barbara J.; Schaefer, Hanne; Salg, Gabriel Alexander; Weigand, Markus A.; Schmitt, Felix; Dietrich, Maximilian; Mohr, Stefan; Küllenberg, Janna; Ries, Markus; Popp, Erik (SSRN eLibrary, 2025)
Study hypothesisMass casualty incidents (MCI) can overwhelm hospital capacities. Effective management requires alarm and deployment plans and exercises to improve familiarity, confidence, and skills. Exercises may benefit the organization as a whole by improving systems, enhancing coordination, leading to a more prepared and efficient response. Scientific evaluation of exercises is crucial to identify their impact, Therefore, this study hypothesized indirect benefits for all staff from MCI exercises, even non-participants.MethodsTwo prospective, representative, anonymous surveys were conducted among all professional groups before and after a full-scale MCI exercise at Heidelberg University Hospital. Descriptive analyses were conducted for the total sample (N=669) and across various group categories. Hierarchical linear regression analyses were performed for the dependent constructs Familiarity with MCI Plan, Familiarity with Alert Process, Knowledge of Tasks, and Knowledge about Roles and Cooperation.ResultsParticipation in an MCI exercise positively influences knowledge of the MCI plan across all four constructs. Employees in management positions and physicians reported higher scores across all constructs. Even staff members who did not take part in the exercises benefited. However, the extent of this effect varies, with greater significance observed for theoretical knowledge than for practical aspects in the context of an MCI exercise.ConclusionsThe study showed significantly improvement of both theoretical and practical knowledge of MCI plan among employees. Even staff members who did not take part in the exercises benefited, probably due to increased awareness and enhanced preparation within the hospital, highlighting their importance in enhancing preparedness.